Acute Renal Failure following Novel Subcutaneous Fat Reduction with Injected Ice Slurry. Issue 7 (12th July 2021) - McMahan, Daniel L.; Dehbozorgi, Hangameh; Lam, Quy N.; Le, Calvin; Richardson, Justin; Villacres, Alexandra; Albaalbaki, Fysal
Abstract : Summary: A new fat-freezing injection may pose significant health risks. Subcutaneous injection of partially frozen normal saline and glycerol has been shown to significantly reduce adipose tissue. This article reports the first human case and adverse reactions following this new procedure.